1987
DOI: 10.1148/radiology.165.2.2958896
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal renal angioplasty in children and adolescents.

Abstract: Percutaneous transluminal renal angioplasty (PTRA) was performed in 12 children and adolescents with renal artery stenosis. Patients were divided into three groups: those with a short stenosis in the middle or distal part of the renal artery (n = 5), those with a short stenosis at or near the origin of the renal artery (n = 3), and those with a long stenosis at or near the origin (n = 4). The patients in the first group responded to PTRA. Those in the second group had a poor clinical response, and dilation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Tyagi et al (17) found that patients with discrete stenosis (≤10 mm) or residual stenosis (≤20%) had a better blood pressure response. Similar results were also reported in another study (18). Supporting the notion that stenosis length is the main determinant of clinical success with PTRA (19), we found that the length of stenosis was significantly shorter in patients who were cured or improved after PTRA treatment than in those who failed to respond to the treatment (8.06±3.10 mm vs. 16.6±5.16 mm, P < 0.01), and our logistic regression analysis showed that the length of stenosis was inversely correlated with the effectiveness rate of PTRA.…”
Section: Discussionsupporting
confidence: 93%
“…Tyagi et al (17) found that patients with discrete stenosis (≤10 mm) or residual stenosis (≤20%) had a better blood pressure response. Similar results were also reported in another study (18). Supporting the notion that stenosis length is the main determinant of clinical success with PTRA (19), we found that the length of stenosis was significantly shorter in patients who were cured or improved after PTRA treatment than in those who failed to respond to the treatment (8.06±3.10 mm vs. 16.6±5.16 mm, P < 0.01), and our logistic regression analysis showed that the length of stenosis was inversely correlated with the effectiveness rate of PTRA.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to medical management, RAS has been traditionally treated with vascular surgery. After the first successful renal artery angioplasty of a child in 1980 [11], there has been growing experience with PTRA in children with RAS during the past several years [12][13][14][15][16][17][18][19]. The success rate of PTRA in children with RAS varies from 25 to 94%.…”
Section: Discussionmentioning
confidence: 99%
“…57 A strong association among NF-1, abdominal aortic coarctation, 1-12,14,16-18,24,52-56 and/or renal ostial stenosis has been reported. [1][2][3][4][5][7][8][9][10][11][13][14][15][16][17][18]24,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Stenoses/aneurysms have been identified also in the visceral, 10,16-19,24,61,71-73 coronary, 23,57 and cerebrovascular circulations 10,28,32,33,[58][59][60] in addition to the thoracic aorta and the subclavian and innominate arteries (see Table 2). 9,25,28,56,…”
Section: Vascular Abnormalitiesmentioning
confidence: 99%